The prevalence of measles among children in Misurata city in the absence of vaccination and the importance of vitamin (A) in the treatment process (Journal of Academic Research, 2020)
Measles is an infectious disease that is transmitted through the respiratory tract and causes the virus Morbillivirus, the symptoms appear in high fever, cough, colds and inflammation of the eye and end with the appearance of skin rashes, and disease a serious health problem  especially  developing countries, they can be combated only through large-scale immunization programs as well as health care and the use of vitamin A supplements, this study was conducted on the data obtained from the statistics department children of Misurata Medical Center in the period from 1 January 2017 to 30 September2019,  suspected cases were identified in this period which reached 65 cases, including 28 cases of measles, the proportion of girls 75% higher than boys 25%, while the most affected age groups less than 5 years, the number of children who visited the center reached 9551 and the number of suspected cases was 33, including 5 cases of the disease. There were no deaths in this period, we find from the results obtained that the most cases were in 2019 and may be due to interruption of vaccination in this year in addition to follow-up of the infected found that most of them were given vitamin A, this is due to using doctor of  supplements to reduce the spread of the disease and the number of deaths.
Keywords: Prevalence of measles; Vaccination; Vitamin A; Misurata